The search for the true self in the Gospel of Thomas, the Book of Thomas and the Hymn of the Pearl - Hartin, Patrick (Hervormde teologiese studies, 1999)
At the heart of the Gospel of Thomas lies the call to achieve an understanding of one's self (Logia 67-70). This call focuses the struggle of Thomas Christians by turning it inward as a challenge to understand their own true identity. Through this struggle they come to a knowledge of the Father. The significance of this theme of the search for the true self is examined further in the context of the Gospel of Thomas (Logia 3; 58; 111). From this study, it emerges that Thomas Christians experienced that they were strangers in a hostile world. Feeling alienated, they wished to escape rom the world. The positive outcome of this experience was a deeper self-understanding. This study culminates in an examination of this theme of the search for one's self in two other writings at home within early Syrian Christianity. In the Hymn of the Pearl (Acts of Thomas 108-113) the theme emerges in the allegory of the soul's quest for self-knowledge. The path to salvation is a search that ultimately takes one rom the world. In the Book of Thomas the Contender the same search for one's identity is emphasised (138:15-20 and 145:1-15). Finally, it is argued that this search for one's true identity is appropriate to the historical and sociological context of the Syrian Church in Edessa.